Answer:
[tex]\dfrac{y^3}{3}\ =\ \dfrac{x^2}{2}+\dfrac{1}{3}[/tex]
Step-by-step explanation:
According to the given question,
The given differential equation is
[tex]xdx\ -\ y^2dy\ =\ 0,\ y(0)\ =\ 1[/tex]
[tex]=>\ xdx\ =\ y^2dy[/tex]
On integrating both sides, we will have
[tex]=>\ \int{xdx}\ =\ \int{y^2dy}[/tex]
[tex]=>\ \dfrac{x^2}{2}\ =\ \dfrac{y^3}{3}+C[/tex] (1)
Now, according to question
y(0)=1
so, we can write
[tex]=>\ \dfrac{x^2}{2}\ =\ \dfrac{y^3}{3}+C[/tex]
[tex]=>\ \dfrac{0^2}{2}\ =\ \dfrac{1^3}{3}+C[/tex]
[tex]=>\ C\ =\ -\dfrac{1}{3}[/tex]
Now, by putting the value of C in equation (1), we will get
[tex]\dfrac{x^2}{2}\ =\ \dfrac{y^3}{3}-\ \dfrac{1}{3}[/tex]
[tex]=>\dfrac{y^3}{3}\ =\ \dfrac{x^2}{2}+\dfrac{1}{3}[/tex]
So, the solution of given differential equation will be
[tex]\dfrac{y^3}{3}\ =\ \dfrac{x^2}{2}+\dfrac{1}{3}[/tex]